2001
DOI: 10.1093/ps/80.3.272
|View full text |Cite
|
Sign up to set email alerts
|

Breeder Age Influences Embryogenesis in Broiler Hatching Eggs

Abstract: The effects of dietary fat and broiler breeder age on egg and embryo characteristics during incubation were investigated. Breeders were fed diets containing no added fat or 3.0% added poultry fat (PF) for peak energy intakes of 430 and 467 kcal/hen day (pC/d), or 1.5% PF or 3.0% corn oil at 449 pC/d. Feeding of diets was initiated at 22 wk, and eggs were collected for incubation at 27 and 36 wk of age. Percentage incubational egg weight loss was determined between day of set and Days 6, 12, and 18. Percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 19 publications
2
20
1
4
Order By: Relevance
“…Lourenço da Silva (1994) stated that the embryo can use about 47% of the eggshell mass during the incubation period, since it provides approximately 80% of the calcium for skeleton formation after D10 (Peebles & Brake, 1985). In the present study, the most striking difference in eggshell thickness was observed on D13, which is consistent with the findings of Peebles et al (2001), who reported a decrease in eggshell weight of eggs produced by 27-and 36-wk-old breeders after D12.…”
Section: Discussionsupporting
confidence: 90%
“…Lourenço da Silva (1994) stated that the embryo can use about 47% of the eggshell mass during the incubation period, since it provides approximately 80% of the calcium for skeleton formation after D10 (Peebles & Brake, 1985). In the present study, the most striking difference in eggshell thickness was observed on D13, which is consistent with the findings of Peebles et al (2001), who reported a decrease in eggshell weight of eggs produced by 27-and 36-wk-old breeders after D12.…”
Section: Discussionsupporting
confidence: 90%
“…Broiler breeder age (Peebles et al 2001) influenced subsequent embryogenesis and hatchability of broilers. Fertility of an egg and embryonic mortality during the hatching process are known to be different for different strains.…”
Section: Introductionmentioning
confidence: 99%
“…Los huevos deben de perder alrededor de 11 a 14 % de su peso original durante el proceso de incubación (Peebles et al, 2001;Suarez et al 1997;Decuypere y Michels 1992;Buhr, 1995;Prado et al 2001). La cutícula ha sido caracterizada como la barrera más externa del huevo para el control de microorganismos ambientales y el intercambio gaseoso y pérdida de agua, a través de los poros durante el desarrollo embrionario (Vick et al 1993;Nys et al, 1999).…”
Section: Discussionunclassified
“…En el presente estudio no se observó diferencia significativa, ya que se utilizó únicamente una edad de reproductora, sin que se afectara por la temperatura de bulbo húmedo (Barbosa et al;2012, French, 19971974;Fasenko et al;2001, Wilson, 1991Burh, 1995;Vick et al;1993;Arce, 1998). Aunque en el presente estudio no mostró diferencia significativa entre los tratamientos en las variables de mortalidad embrionaria, se puede apreciar que hay un aumento considerable de mortalidad embrionaria en los primeros días de incubación, puede ser asociado a las condiciones del manejo de todos los huevos en general, ya que la granja de reproductora se localiza a una distancia de 1 000 kilómetros de retirada de la planta incubadora; por lo que el transporte puede estar influyendo de manera significativa.…”
Section: Discussionunclassified
See 1 more Smart Citation